2018
DOI: 10.3390/c4010010
|View full text |Cite
|
Sign up to set email alerts
|

Surface Observation and Magnetism of Oil-Extracted Botryococcus braunii Residues before and after Carbonization

Abstract: Abstract:Microalgae is a promising next-generational energy. In this research, we focus on oil-extracted Botryococcus braunii residues collected by adding polysilicato-iron (PSI) as a flocculant followed by carbonization under argon atmosphere. We conducted carbonization at various temperatures as a first attempt to reveal the fundamental properties of the carbonization process of the microbes. The carbons thus obtained by heat treatment at 900 • C present a unique magnetic behavior due to reduced magnetite (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…Figure e shows the temperature dependence of χ for PANI ES and PANI/HPC. PANI in PANI/HPC exhibited paramagnetism as χ increased with a decrease in temperature. , Temperature dependence of χ T (magnetic susceptibility × temperature, Curie plots) for PANI ES (Figure f) and PANI/HPC (Figure g) indicated that χ T values of PANI ES and PANI/HPC are constant below 300 K, which is consistent with the Curie–Weiss law, confirming that both PANI ES and PANI/HPC is paramagnetic. , χ value per weight of PANI/HPC is small compared to that of PANI ES as a pure PANI sample. This may be due to the fact that the spin species of PANI/HPC is distributed in the HPC matrix, and the main chain of PANI and the polaron arrange in a helical manner in the HPC matrix, resulting in a decrease of the concentration of spin species in the HPC matrix and depression of the entire magnetic moment of the sample by helical arrangement of spin species through cancelling out the spins facing the opposite direction in the helix.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Figure e shows the temperature dependence of χ for PANI ES and PANI/HPC. PANI in PANI/HPC exhibited paramagnetism as χ increased with a decrease in temperature. , Temperature dependence of χ T (magnetic susceptibility × temperature, Curie plots) for PANI ES (Figure f) and PANI/HPC (Figure g) indicated that χ T values of PANI ES and PANI/HPC are constant below 300 K, which is consistent with the Curie–Weiss law, confirming that both PANI ES and PANI/HPC is paramagnetic. , χ value per weight of PANI/HPC is small compared to that of PANI ES as a pure PANI sample. This may be due to the fact that the spin species of PANI/HPC is distributed in the HPC matrix, and the main chain of PANI and the polaron arrange in a helical manner in the HPC matrix, resulting in a decrease of the concentration of spin species in the HPC matrix and depression of the entire magnetic moment of the sample by helical arrangement of spin species through cancelling out the spins facing the opposite direction in the helix.…”
Section: Resultssupporting
confidence: 60%
“…PANI in PANI/HPC exhibited paramagnetism as χ increased with a decrease in temperature. 28,29 Temperature dependence of χT (magnetic susceptibility × temperature, Curie plots) for PANI ES (Figure 4f) and PANI/HPC (Figure 4g) indicated that χT values of PANI ES and PANI/HPC are constant below 300 K, which is consistent with the Curie−Weiss law, confirming that both PANI ES and PANI/HPC is paramagnetic. 30,31 χ value per weight of PANI/ HPC is small compared to that of PANI ES as a pure PANI sample.…”
Section: ■ Experimental Sectionmentioning
confidence: 86%
“…We have mentioned in our previous report that the syngas such like hydrogen gas or carbon monoxide gas would be the trigger of the reduction reaction for the formation of polygonal crystal which consists of Fe 3 O 4 or α-Fe inside [16]. Figure SI2(d), two hexagonal disks with a very small hexagon were found on the edge of bulk sample, indicating that the crystals are on the process of growth.…”
Section: Sem Observationmentioning
confidence: 78%
“…In our previous study, we reported that different carbonization condition would affect the morphology of the yielded crystals [16]. Polygonal grains were observed in the sample carbonized above 700˚C under argon atmosphere.…”
Section: Introductionmentioning
confidence: 93%